ANALISIS PENERAPAN METODE SQ3R SEBAGAI UPAYA MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN BAHASA JERMAN SISWA KELAS X SMA - Mustakim, Yehory Yoshy; Samsul, Suwarno Imam (LATERNE, 2022)
Foreign language skills are one of the things that are needed today because there are no more restrictions that allow anyone from any part of the world to freely obtain information. Most schools in Indonesia have included foreign languages as taught subjects, such as German. Tarigan (2015: 1) stated that in language there are four skills that must be mastered, one of which is reading. However, in reading German there are some difficulties encountered, such as articles on nouns that students must memorize and also differences in sentence structure that also change depending on the case, and the ability to understand the contents of the reading is required. Thus, to help students overcome difficulties in learning German, the right method is needed, namely the SQ3R method (Survey, Question, Read, Recite, Review). This method has stages that can overcome difficulties in reading comprehension of the German language. The writing of this article is done by analyzing the application of the SQ3R method in an effort to improve the reading skills of German comprehension of high school class X students. This research uses the descriptive qualitative method by doing inductive reasoning to related literature sources. The results obtained are SQ3R method is a method that can be used by teachers as a solution to overcome the difficulties of reading students ’German comprehension, improve students’ German comprehension reading skills, and improve critical thinking skills.